Nationalism, Militarism and Masculinity in Post-Conflict Cyprus - Efthymiou, Stratis Andreas; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book uses empirical research to introduce the relationship between nationalism, militarism and masculinity. The co-constitution between these three factors is susceptible to change and hinders reconciliation, according to the author. Drawing on the case of Cyprus, a country in conflict with Turkey, Efthymiou reveals how nationalism, militarism and masculinity were constructed after the war, and re-adapted following the opening of internal borders and European Union accession. Nationalism, Militarism and Masculinity in Post-Conflict Cyprus draws on rich field-research, with soldiers and officers in army barracks, politicians such as former President of Republic of Cyprus Glafkos Clerides, leaders of radical far-right movements and the Greek Cypriot public. The book offers invaluable insight into the application of nationalism, militarism and masculinity in governmental policy including by the Cyprus Defence Ministry, and will be of interest to students and scholars in sociology, gender studies, peace studies, security studies, politics and international relations, as well as governments and NGOs.
Keywords: Political sociology; Sex; Politics and war; Political Sociology; Gender Studies; Military and Defence Studies